Understanding Technology and People Issues in Hospital Information System (HIS) Adoption: Case study of a tertiary hospital in Malaysia - Nasriah Zakaria; Shafiz Affendi Mohd Yusof (Elsevier, 2016)
Summary: Background: Hospital Information Systems (HIS) can improve healthcare outcome quality, increase efficiency, and reduce errors. The government of Malaysia implemented HIS across the country to maximize the use of technology to improve healthcare delivery, however, little is known about the benefits and challenges of HIS adoption in each institution. This paper looks at the technology and people issues in adopting such systems. Methods: The study used a case study approach, using an in-depth interview with multidisciplinary medical team members who were using the system on a daily basis. A thematic analysis using Atlas.ti was employed to understand the complex relations among themes and sub-themes to discover the patterns in the data. . Results: Users found the new system increased the efficiency of workflows and saved time. They reported less redundancy of work and improved communication among medical team members. Data retrieval and storage were also mentioned as positive results of the new HIS system. Healthcare workers showed positive attitudes during training and throughout the learning process. Conclusions: From a technological perspective, it was found that medical workers using HIS has better access and data management compared to the previously used manual system. The human issues analysis reveals positive attitudes toward using HIS among the users especially from the physicians' side. Keywords: HIS adoption, Technology and people issues, Case study